The Formation of Islam, Dayak, Banjar, and Bakumpai Identity Maintaining in Buntok, Central Kalimantan, Indonesia - Yusriadi, Yusriadi (The Pontianak State Institute of Islamic Studies, 2020)
Religion and culture are important ingredients in the formation of ethnic identities. When the dynamics of ethnicity move smoothly, religion and culture are used as materials to identify oneself and other groups; as the same or different groups. This article intends to look at how the identity of the Bakumpai people in South Barito, Central Kalimantan, and how the flower of Islam is included in the construction of the group's identity. Data obtained from field research on the Bakumpai people in Buntok, South Barito, Central Kalimantan, through interviews with a number of sources and field observations. This study concludes that elements of Islam and culture are important ingredients in maintaining Bakumpai's identity. Islam and culture make Bakumpai different from the Dayak (Ngaju) and Banjar people. Islam differentiates the Bakumpai people from the Dayak people - especially the Ngaju, while culture and language are used to identify similarities between them. On the other hand, religion makes the Bakumpai people have the same identity with the Banjar people. Culture and language makes their identity different.